Classical archaeology at the University of Zadar (Archaeologia Adriatica, 2013)
A concise overview of the Chair in Classical Archaeology is given with emphasis on main achievements of excavations, scientific studies and lectures on Greek and Roman periods at the University of Zadar. Contribution of four eminent scholars was presented briefly: Mate Suić, Branimir Gabričević, Julijan Medini and Nenad Cambi. Highlights of recent activities at the Chair and direction of future development were delineated.
Keywords: Chair in Classical Archaeology; fifty years of the Department of Archaeology; University of Zadar